Faktor yang Mempengaruhi Kekurangan Energi Kronis (KEK) pada Ibu Hamil di Desa Belaras Kecamatan Khairiah Mandah Kota Tembilahan - Rizki Natia Wiji; Nurmala Sary; Silvia Anita Yuningsih; Heni Heriyeni (Program Studi Gizi UNSIKA, 2022)
To prevent the risk of chronic energy deficiency (KEK) in pregnant women before pregnancy women of childbearing age must have good nutrition, for example the Upper Arm Circle (LILA) is not less than 23.5 cm. So that research is carried out with the aim to determine the factors that influence chronic energy deficiency (KEK) in pregnant women in Belaras Village, Khairiah Mandah District, Tembilahan City. This type of research is analytic with cross sectional design. With a sample of 82 pregnant women where the sample was taken by purposive sampling technique. Collecting data using a questionnaire, data were analyzed using chi square statistical test with 95% confidence degree. The results showed that the independent variables were the number of intakes of pregnant women (p-value 0.012), maternal age (p-value 0.028) and maternal knowledge (p-value 0.019) there is a significant relationship with the dependent variable, namely the incidence of KEK in pregnant women. It is recommended for pregnant women to pay more attention to their diet and the amount of daily nutritional intake needed to avoid BBLR birth and experience KEK. Keyword: Chronic Energy Deficiency (KEK)